Draft Genome Sequence of Bacillus cereus LCT-BC25, Isolated from Space Flight - Zhang, Xuelin (American Society for Microbiology, 2014)
Bacillus cereus strain LCT-BC25, which was carried by the Shenzhou VIII spacecraft, traveled in space for about 398 h. To investigate the response of B. cereus to space environments, we determined the genome sequence of B. cereus strain LCT-BC25, which was isolated after space flight.